ANALISIS ALGORITMA PREDIKSI UNTUK MENGHASILKAN PREDIKSI BEBAN LISTRIK JANGKA PENDEK - Veti Apriana; Rani Irma Handayani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
Electricity is the lifeblood for human life, both for household and industrial world. In the power supply industry, it is important to determine the power requirements for the future as soon as possible (at the earliest). Short-term electric load prediction is one way that can be used to generate and distribute electrical energy economically so that the power provider can know the load and demand for power for the next month, previous short-term power prediction studies, generally using the Neural method Network. Neural Network is an information processing system that has characteristics similar to biological neural networks but, deficiencies in Neural Network often overfitting due to overtraining. In a short-term electrical load prediction study, using the Support Vector Machine (SVM) method, Support Vector Machines (SVM) is a technique for predicting both classification and regression. This research begins by processing daily load system load data with a time span of 30 minutes, with data input used is data in January 2017. The results show that the SVM method can be one of the reference methods for the prediction of short-term electrical load with RMSE 0.034.